Science Learning and Instruction : Taking Advantage of Technology to Promote Knowledge Integration. - Linn, Marcia C. (Taylor & Francis, 2011)
This book describes advances in understanding the nature of science learning and their implications for the design of science instruction, showing how design patterns, design principles, and professional development opportunities coalesce to create and sustain effective instruction.